The Influence of Demonstration Methods with Media on Mathematics Learning Outcomes SDN 091546 Unong Manik, Simalungun Regency - Alexander Samosir; Ficha Aulia Nanda (PT Inovasi Pratama Internasional, 2022)
Mathematics is the science that underlies the development of modern technology. Mathematics has a role in various other disciplines, and advances human thinking. One of the learning methods that apply real learning aids is the demonstrass method. Demonstration method is a learning method that shows the object, the process of something being studied, accompanied by a brief explanation from the teacher and the participation of students in learning. The researcher formulates the problem as follows. Is there an effect of the use of demonstration methods with the media on mathematics learning outcomes in fifth grade students at SD Negeri 091546 Unong Manik? The research design used in this study was a one group pre-post test design. What is studied is the process of implementing learning, the increase that occurs from pretest to posttest, the effect of the demonstration method with the media on student learning outcomes using the demonstration method which is then compared with the two-way ANOVA test. Mathematics lessons before learning using the Demonstration method with the media reached 48, 68 were included in the almost sufficient category. Based on the t-test, the t-count results showed 1.553 with a p value of 0.129 0.05 meaning that there was an effect of the Demonstration method with the media on student learning outcomes in learning Mathematics for class V SD Negeri 091546 Unong Manik Semester 1 (even) Academic Year 2017/2018 After conducting research and data processing it can be concluded that the application of the demonstration method in learning mathematics affects student learning outcomes. Suggestions from researchers, demonstration methods can be used by teachers in learning activities to create an active learning atmosphere and to improve student learning outcomes.